Comparison of median nerve stiffness with and without rheumatoid arthritis by ultrasound real-time tissue elastography: A propensity score matching study. Issue 3 (3rd May 2020) - Anno, Shohei; Okano, Tadashi; Mamoto, Kenji; Sugioka, Yuko; Takeda, Setsuko; Hashimoto, Ayumi; Yamashita, Emi; Morinaka, Rika; Ueda, Hatsue; Inui, Kentaro; Koike, Tatsuya; Nakamura, Hiroaki
Abstract: Objectives: This study aimed to compare median nerve stiffness measured by ultrasound real-time tissue elastography in patients with and without rheumatoid arthritis (RA and non-RA groups, respectively). Methods: Altogether, 402 hands of 201 RA group and 222 hands of 111 non-RA group were included in the study. Ultrasonography was performed to evaluate the circumference, cross‐sectional area (CSA) and strain ratio as an elasticity of the median nerve at the inlet level of the carpal tunnel and the proximal portion of the carpal tunnel inlet. Using propensity score matching, the difference between RA and non-RA group were analyzed. Results: After propensity score matching, 135 hands in 104 RA group and 70 non-RA group were finally analyzed. There were no significant differences in the circumference and CSA of the median nerve between the two groups. The strain ratio of the median nerve was significantly higher in RA group than in non-RA group only at the inlet of the carpal tunnel level. Conclusions: The nerve stiffness in patients with RA measured by ultrasound real-time tissue elastography was higher than without RA. Inflammatory condition of the flexor tendon and wrist joint in patients with RA may generate fibrotic changes in the median nerve. Trial registration: University Hospital Medical Information Network Clinical Trials Registry: UMIN000015314.